Magnetic coupling engineered porous dielectric carbon within ultralow filler loading toward tunable and high-performance microwave absorption. (20th April 2021) - Yang, Wang; Jiang, Bo; Liu, Zhihui; Li, Rui; Hou, Liqiang; Li, Zhengxuan; Duan, Yongli; Yan, Xingru; Yang, Fan; Li, Yongfeng
Graphical abstract: A lightweight microwave absorber constructed by hierarchically porous carbon with firmly embedded magnetic nanoparticles achieves an excellent microwave absorption performance with an ultralow filler loading of 5 wt.%, which outperforms the current magnetic-dielectric hybrids. Highlights: A feasible strategy is proposed to construct hierarchical porous magnetic carbon with tightly embedded Ni species. Well-dispered Ni nanoparticles produce strong magnetic coupling networks to enhance magnetic loss of dielectric carbon. The absorbers exhibit an excellent microwave absorption performance with an ultralow filler loading of 5 wt.%. This work unfolds a new avenue for the development of high-performance and lightweight microwave absorbers. Abstract: Developing microwave absorption (MA) materials with satisfied comprehensive performance is a great challenge for tackling severe electromagnetic pollution. In particular, the magnetic component/carbon hybrids absorbers always suffer from high filler loading. Herein, we propose a feasible strategy to construct hierarchical porous carbon with tightly embedded Ni nanoparticles (Ni@NPC). These highly dispersed Ni nanoparticles produce strong magnetic coupling networks to enhance magnetic loss abilities. Moreover, the interconnected hierarchical dielectric carbon network affords favorable dipolar/interfacial polarization, conduction loss, multiple reflection and scattering. Impressively, with an ultralow filler loading of 5 wt.%, the resultant Ni@NPC/paraffin composite achieves an excellent MA performance with a minimum reflection loss of as high as -72.4 dB and a broad absorption bandwidth of 5.0 GHz. This capability outperforms most current magnetic-dielectric hybrids counterparts. Furthermore, the MA capacity can be easily tuned with adjustments in thickness, content and type of magnetic material. Thus, this work opens up new avenues for the development of high-performance and lightweight MA materials.